2019
DOI: 10.1096/fj.201900880r
|View full text |Cite
|
Sign up to set email alerts
|

Fam20C‐mediated phosphorylation of osteopontin is critical for its secretion but dispensable for its action as a cytokine in the activation of hepatic stellate cells in liver fibrogenesis

Abstract: Amedeo Carraro and Anna Maria Brunati are co-senior authors.Abbreviations: BDL, bile duct ligation; CK1, casein kinase1; ECM, extracellular matrix; ER, endoplasmic reticulum; Fam20A, family with sequence similarity 20, member A; Fam20C, family with sequence similarity 20, member C; F/P, FBS combined with PDGF; FBS, fetal bovine serum; GRP94, glucose related protein 94; GRP78/BiP, glucose related protein78; HSCs, hepatic stellate cells; OPN, osteopontin; PDI, protein disulfide isomerase; PDGF, platelet-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The phosphorylation of serine residues arranged in a similar motif in osteopontin has been linked to its secretion. 35 Considering this, we first examined whether in cultured cells, the mutated protein can be expressed, localized, and secreted in a comparable manner to that of the native protein. Because of the unavailability of a suitable antibody to detect mouse MGP in immunodetection techniques, we tagged both wild type and mutated MGP with the FLAG tag.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of serine residues arranged in a similar motif in osteopontin has been linked to its secretion. 35 Considering this, we first examined whether in cultured cells, the mutated protein can be expressed, localized, and secreted in a comparable manner to that of the native protein. Because of the unavailability of a suitable antibody to detect mouse MGP in immunodetection techniques, we tagged both wild type and mutated MGP with the FLAG tag.…”
Section: Discussionmentioning
confidence: 99%
“…Cytidine deaminase (CDA) is an enzyme that plays a crucial role in the pyrimidine salvage pathway ( 71 ). Family with sequence similarity 20 member C (FAM20C), previously known as Golgi casein kinase (G-CK), is a protein specifically localized in the Golgi apparatus ( 72 ). NELL2 is a glycoprotein involved in the development of neural cells and guidance of axons, including their repulsion ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…FAM20C promotes the phosphorylation of secretory proteins under diverse physiological and pathological conditions. These proteins participate in the interaction between the ER and the GA. FAM20C is involved in the supramolecular mechanism directing protein sorting and promoting the appropriate molecule conformation outside the cell ( 172 ). It is suggested that the pathological inhibition of FAM20C can inhibit abnormal protein sorting.…”
Section: Therapeutic Strategies Targeting Spkkpsmentioning
confidence: 99%